The beginning of knowledge - Gadamer, Hans-Georg (Continuum, 2001)
In this work Gadamer reminds us that philosophy for the Greeks was not just a question of metaphysics and epistemology but encompassed cosmology, physics, mathematics, medicine and the entire reach of theoretical curiosity and intellectual mastery. Whereas Gadamer's book "The Beginning of Philosophy" dealt with the inception of philosophical inquiry, this book brings together nearly all of his previously published but never translated essays on the Presocratics. Beginning with a hermeneutical and philological investigation of the Heraclitus fragments (1974 and 1990), he then moves on to a discussion of the Greek Atomists (1935) and the Presocratic cosmologists (1964). In the last two essays (1978 and 1994/95), Gadamer elaborates on the profound debt that modern scientific thinking owes to the Greek philosophical tradition.